2010
DOI: 10.1177/0093854810361672
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Misconduct and Differential Parole Eligibility Among Capital Inmates

Abstract: Managing career inmates (e.g., capital murderers) is a serious burden for prison administrators and taxpayers. Research findings are mixed as to whether such inmates will engage in increased levels of institutional misconduct. Using complete disciplinary histories from non-death-sentenced capital inmates in Texas whose offenses occurred between 1987 and 1994, the authors explored the need for increased security levels between capital murderers sentenced to markedly different parole eligibility policies (15 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
63
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 83 publications
10
63
0
Order By: Relevance
“…Specifically, the likelihood of prisoner misconduct and the frequency of rule violations are examined across those sentenced under an indeterminate punishment policy and those required to serve a determinate sentence of a minimum of 85% of the court imposed sentence. While there is some scholarship which has examined the impact of determinate punishment on prisoner misconduct (Cao, Zhao, & Van Dine, 1997;Emshoff & Davidson, 1987;Forst & Brady, 1983;Goodstein et al, 1984;Memory et al, 1999;Morris et al, 2010;Sorensen & Wrinkle, 1996), this paper expands and improves upon prior studies in several substantive ways. First, the change from indeterminate to determinate punishment in Florida is well documented and there is a definitive demarcation when this change occurred.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Specifically, the likelihood of prisoner misconduct and the frequency of rule violations are examined across those sentenced under an indeterminate punishment policy and those required to serve a determinate sentence of a minimum of 85% of the court imposed sentence. While there is some scholarship which has examined the impact of determinate punishment on prisoner misconduct (Cao, Zhao, & Van Dine, 1997;Emshoff & Davidson, 1987;Forst & Brady, 1983;Goodstein et al, 1984;Memory et al, 1999;Morris et al, 2010;Sorensen & Wrinkle, 1996), this paper expands and improves upon prior studies in several substantive ways. First, the change from indeterminate to determinate punishment in Florida is well documented and there is a definitive demarcation when this change occurred.…”
Section: Introductionmentioning
confidence: 80%
“…Prior research of misconduct across male and female inmates has yielded mixed results, with some finding lower levels of rule infractions by females (Craddock, 1996;Goetting & Howsen, 1986), and others discovering that females are more likely to violate prison rules (Cao, Zhao, & Van Dine, 1997;Lindquist, 1980). Inmates sentenced to longer sentences or life without parole or death, have been found to be less likely to commit rule infractions (Cunningham, Reidy, & Sorensen, 2005;Morris et al, 2010). Some researchers have found that prisoners tend to commit more rule violations earlier during their stay in prison (Bottoms, 1999;Craddock, 1996).…”
Section: General Correlates Of Inmate Misconductmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have observed that a longer criminal history or history of other antisocial behavior (e.g., drug use, association with antisocial peers) is related to maladjustment (Andia et al, 2005;Arbach-Lucioni et al, 2012;Berg & DeLisi, 2006;Berk, Kriegler, & Baek, 2006;Cunningham & Sorensen, 2006;Drury & DeLisi, 2008;Gaes, Wallace, Gilman, Klein-Saffran, & Suppa, 2002;Griffin & Hepburn, 2006;Steiner & Wooldredge, 2009a, 2009b. Involvement in conventional behaviors may aid adjustment among inmates, and researchers have examined the effects of education, marital status, and prearrest employment on maladjustment, but the evidence concerning these variables has been mixed (e.g., Andia et al, 2005;Huebner, 2003;Jiang & Winfree, 2006;Morris et al, 2010;Steiner & Wooldredge, 2009a, 2009b. Related studies have also found that having children may be an important influence on adjustment (Gover, Perez, & Jennings, 2008;Jiang & Winfree, 2006;Steiner & Wooldredge, 2009a).…”
Section: Other Known Correlates Of Inmate Maladjustmentmentioning
confidence: 99%
“…A final predictor of violent misconduct related to the importation model concerns the effect of prior incarceration. Some have reported that prior incarcerations increased the likelihood of misconduct (Cunningham & Sorensen, 2006a;2007;Griffin & Hepburn, 2006;Jiang & Winfree, 2006;Lahm, 2008;Sorensen & Pilgrim, 2000;Wooldredge et al, 2001) while others have found a negative or null effect for certain types of inmates (Cao et al, 1997;Morris, Longmire, Buffington-Vollum, & Vollum, 2010;Wolfgang, 1961;Wooldredge, 1994).…”
Section: The Importation Perspectivementioning
confidence: 99%